2004
DOI: 10.2337/diacare.27.12.2948
|View full text |Cite
|
Sign up to set email alerts
|

Visceral and Central Abdominal Fat and Anthropometry in Relation to Diabetes in Asian Indians

Abstract: FNASCOBJECTIVE -The objective of the study was to examine body fat distribution using computed tomography (CT), dual-energy X-ray absorptiometry (DEXA), and anthropometry in relation to type 2 diabetes in urban Asian Indians. RESEARCH DESIGN AND METHODS-This is a case-control study of 82 type 2 diabetic and 82 age-and sex-matched nondiabetic subjects from the Chennai Urban Rural Epidemiology Study, an ongoing epidemiological study in southern India. Visceral, subcutaneous, and total abdominal fat were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
110
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 27 publications
7
110
1
5
Order By: Relevance
“…Moreover, most existing studies of SA have focused on Indians (8,14,17,18,(30)(31)(32) , neglecting other groups of SA. The present work represents one of only a few studies to examine MetS prevalence (and the prevalence of abnormal indicators) in the USA in a large sample of SA Americans of different ethnicities and use the newer suggested cut-offs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most existing studies of SA have focused on Indians (8,14,17,18,(30)(31)(32) , neglecting other groups of SA. The present work represents one of only a few studies to examine MetS prevalence (and the prevalence of abnormal indicators) in the USA in a large sample of SA Americans of different ethnicities and use the newer suggested cut-offs.…”
Section: Discussionmentioning
confidence: 99%
“…These prevalences are lower than those recently reported in the USA by Khanna et al (77 %) (18) , similar to those found by Ramachandran et al (41 %) (4) and lower than those observed by Flowers et al and Dodani et al (27 %) (23,33) who also used the harmonized WC cut-offs. Prior to the advent of the new harmonized definition, it had been difficult to compare studies of SA since different researchers used different MetS definitions (1,10,34) , various cut-offs (17,(35)(36)(37) as well as different measures of obesity (WC v. waist-to-hip ratio v. BMI) (12,14,21,38) for MetS.…”
Section: Discussionmentioning
confidence: 99%
“…Central obesity has a strong correlation with cardiovascular disease [1] and has been linked to Alzheimer's disease and type 2 diabetes [2], as well as other metabolic and vascular diseases [3]. Enzyme cholinesterase is present in all mammals and two classes have been identified as acetylcholinesterase (AChE, EC 3.1.1.7) and butyrylcholinesterase (non-specific, pseudocholinesterase, BChE; EC 3.1.1.8) in serum.…”
Section: Introductionmentioning
confidence: 99%
“…Com isso, as dislipidemias e a hiperglicemia, causadas pela obesidade e pela inatividade física, estão fortemente associadas com o risco de maior probabilidade para desenvolver doenças cardiovasculares, sendo que as gorduras viscerais estão associadas com efeitos negativos à saúde, independentemente da quantidade de gordura corporal, isto é, mesmo o indivíduo apresentando um Índice de Massa Corporal (IMC) normal, ainda há riscos de arteriosclerose (CASTRO et al, 2004;COSTA et al, 2007;ANJANA et al, 2004).…”
Section: Introductionunclassified